2010
DOI: 10.1371/journal.ppat.1001075
|View full text |Cite
|
Sign up to set email alerts
|

C. elegans SWAN-1 Binds to EGL-9 and Regulates HIF-1-Mediated Resistance to the Bacterial Pathogen Pseudomonas aeruginosa PAO1

Abstract: Pseudomonas aeruginosa is a nearly ubiquitous human pathogen, and infections can be lethal to patients with impaired respiratory and immune systems. Prior studies have established that strong loss-of-function mutations in the egl-9 gene protect the nematode C. elegans from P. aeruginosa PAO1 fast killing. EGL-9 inhibits the HIF-1 transcription factor via two pathways. First, EGL-9 is the enzyme that targets HIF-1 for oxygen-dependent degradation via the VHL-1 E3 ligase. Second, EGL-9 inhibits HIF-1-mediated ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
87
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(90 citation statements)
references
References 58 publications
3
87
0
Order By: Relevance
“…hif-1-dependent upregulation of lys-7 is essential for increased thermotolerance of the flcn-1-mutant strain over WTN2, providing a possible regulator downstream of hif-1. Moreover -because lys-7 encodes an antimicrobial lysozyme -this finding provides another putative link between hif-1 and the defense against bacterial pathogens (Shao et al, 2010;Luhachack et al, 2012). Yet, the question whether hif-1 is an essential mediator of longevity in flcn-1-mutant worms or whether the mere presence of hif-1 is required for this phenotype cannot be finally answered.…”
Section: Discussionmentioning
confidence: 99%
“…hif-1-dependent upregulation of lys-7 is essential for increased thermotolerance of the flcn-1-mutant strain over WTN2, providing a possible regulator downstream of hif-1. Moreover -because lys-7 encodes an antimicrobial lysozyme -this finding provides another putative link between hif-1 and the defense against bacterial pathogens (Shao et al, 2010;Luhachack et al, 2012). Yet, the question whether hif-1 is an essential mediator of longevity in flcn-1-mutant worms or whether the mere presence of hif-1 is required for this phenotype cannot be finally answered.…”
Section: Discussionmentioning
confidence: 99%
“…By driving expression of genes involved in host immunity and inflammation, studies with HIF-1α knockout mice revealed that activation of HIF-1 after pathogen interaction (Group A Streptococcus, Yersinia enteroletica or P. aeruginosa) is essential for a full inflammatory response in the host (15)(16)(17). However, as we know, CF-affected cells have imbalanced inflammatory responses during infection.…”
Section: Discussionmentioning
confidence: 99%
“…The physiological importance of HIF-1α in humans is underscored by the fact that mutations in VHL, the von HippelLindau tumor suppressor gene, which encodes an E3-ubiquitin ligase component required for the degradation of HIF-1, lead to an inherited form of cancer (18,19). HIF-1 regulates adaptation to low oxygen and various other biological processes, including axon guidance, immunity, iron homeostasis, and aging (20)(21)(22)(23)(24)(25)(26)(27)(28)(29). Increased levels of HIF-1 by vhl-1 mutations or by overexpression of HIF-1 lengthen the lifespan of C. elegans (27,28).…”
mentioning
confidence: 99%